The Influence of Profitability and Good Corporate Governance on Firm Value: The Moderating Role of Firm Size - Wijaya, Angelina Christine Abdi; Ernawati, Sri; Asyikin, Jumirin; Syam, Akhmad Yafiz (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2026)
This study aims to examine the effect of profitability and Good Corporate Governance (GCG) on firm value, with firm size acting as a moderating variable, in pharmaceutical companies listed on the Indonesia Stock Exchange during the 2021–2024 period. The background of this research is the fluctuation in firm value within the pharmaceutical sector following the post-pandemic period, indicating that financial and governance factors may influence market perceptions. This study employs a quantitative approach using secondary data obtained from annual reports and corporate governance reports. The sample consists of 33 firm-year observations selected through purposive sampling. The data were analyzed using multiple linear regression and Moderated Regression Analysis (MRA). The results show that profitability has a positive and significant effect on firm value, indicating that investors respond positively to the company’s ability to generate profits. Meanwhile, Good Corporate Governance does not have a significant individual effect, although it contributes simultaneously within the regression model. Furthermore, firm size is not proven to moderate the relationship between profitability and GCG on firm value. These findings suggest that investors in the pharmaceutical sector place greater emphasis on financial performance than on governance structure when assessing firm value.